2011
DOI: 10.3233/jvr-2011-0552
|View full text |Cite
|
Sign up to set email alerts
|

Special education teachers serving students with autism: A descriptive study of the characteristics and self-reported knowledge and practices employed

Abstract: Autism now affects a significant number of students in schools. The purpose of this study was to survey special education teachers who serve students with autism to 1) determine teacher, environmental, and student related characteristics; 2) identify the self-reported knowledge of effective teaching practices; and 3) identify the self-reported implementation of effective teaching practices. The study was conducted with special education teachers employed in Virginia using a web-based survey titled the Needs As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 27 publications
3
32
0
5
Order By: Relevance
“…A similar profile was reported in studies conducted by Toran et al and Wei et al 15,16 A moderate level of self-reported competency in determining appropriate intervention goals for the autistic children was reported by respondents in our study. Hendricks , Toran et al and Wei et al noted similar findings in their studies 9,14,16 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A similar profile was reported in studies conducted by Toran et al and Wei et al 15,16 A moderate level of self-reported competency in determining appropriate intervention goals for the autistic children was reported by respondents in our study. Hendricks , Toran et al and Wei et al noted similar findings in their studies 9,14,16 .…”
Section: Discussionsupporting
confidence: 65%
“…This research adapted the same questionnaire used by Hendricks in the study 'Skill competencies for professionals and paraprofessionals in Virginia supporting individuals with autism across the lifespan' 9 . This questionnaire was used to survey special education teachers employed in public schools in Virginia, USA The Virginia Skill Competencies is a list of guidelines for educators who serve students with autism and it was generated to develop educational standards in autism 10 .…”
Section: Questionnairementioning
confidence: 99%
“…It is worrying that the majority of primary school teachers appeared to have poor knowledge about autistic children (Geraldina, 2015), were not prepared to teach autistic children in their classroom (Cramer, 2014;Low et al, 2017;Pervin, 2016;Razali et al, 2013) and felt inadequate in both teaching and dealing with students with autism (Akgul, 2012;Toran et al, 2016). Furthermore, teachers expressed neutral attitudes towards the inclusion of students with autism in general education classrooms (Engstrand & Roll-Pettersson, 2012;Srivastava et al, 2017a), whereas special education teachers, who taught students with autism, had low to moderate levels of knowledge regarding autism, as well as low to moderately effective teaching practices for their students (Hendricks, 2011). Finally, in-service, preservice, and future teachers had no (or limited) knowledge as well as basic misconceptions about autism and the needs of students with autism in inclusive education classes (Ayub et al, 2017;Barned et al, 2011;Finch et al, 2013;Johnson et al, 2012;Rakap et al, 2016;Yasar & Cronin, 2014;Young et al, 2017).…”
Section: Discussion -Conclusionmentioning
confidence: 99%
“…However, 75% of the sample reported that full inclusion was not feasible for all the students. Hendricks (2011) in the state of Virginia analysed the knowledge and practices of 498 special education teachers about autism. Interestingly, this survey's results revealed that special education teachers, who were teaching students with autism, had low to moderate levels of knowledge regarding autism, as well as low to moderate effective teaching practices for their students.…”
Section: United States Of Americamentioning
confidence: 99%
“…The National Research Council (NRC, 2001) concluded that current teachers' preparation programs designed to prepare teachers to work with children with autism is the weakest point in these programs. Hendricks (2011) indicates that this weakness comes from the special nature of these children. Preparation programs (pre-and in-service) require specialized training in order to provide teachers with the needed competences to understand these students' characteristics and to respond to the needs that results from them.…”
Section: Introductionmentioning
confidence: 99%